Identifikasi dan Karakterisasi Sumber Daya Genetik Buah-Buahan Lokal di Kabupaten Badung - SUDARMIKA, I GEDE; RAI, I NYOMAN; UTAMI, UTAMI (Agrotrop : Journal on Agriculture Science; Vol 6 No 2 (2016), 2016)
Identification and Characterization of Genetic Resources of Local Fruits inBadung Regency. Local fruit are all species of fruits developed and cultivated in Bali,while the local fruit products are all productsderived from fruit plants that are still fresh orthat have been processed. This study aimed to identify the species of genetic resources oflocal fruits in Badung Regency, profiling the genetic resources concerning the morphologicalcharacters, usebility, production, superior fruit, harvest fruit, and geographic distribution mapsof genetic resources. The research was done in all Districts in Badung regency, Province ofBali, namely Petang, Mengwi, Abiansemal, North Kuta, Kuta and South Kuta. Conductedfrom February to September 2015. The research consisted of collecting secondarydata,collecting primary data, surveying genetic resources and species distribution, determiningmorphological characters, determining the superior fruit, and compiling geographical maps.The research found 34 species and 51 sub-species of local fruits in six districts. Based on thevalue of Location Quotient Badung Regency has eight superior fruits commodied that areavocado, durian, guava, jackfruit, pineapple, banana, sapodilla, and watermelon.
Keywords: Characterization, Genetic Resources, Identification, Local Fruits